GAMBARAN DUKUNGAN SOSIAL DARI GURU YANG DIRASAKAN OLEH SISWA SMA “X” - Rahmaputri, Anisah Aninditya; Kusumawardhani, Dianti Endang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
Teachers have an important role in educating students well. One way that teachers can do to be able to increase motivation and school engagement is by providing social support to students. This study aims to find out the overview of perceived social support from teachers by high school “X” students in South Tangerang. The research method is descriptive qualitative research with data collection techniques through focus group discussions and structured interviews. The results of data retrieval show that the perceived social support from some teachers by high school